Tourism planning in Spain. From traditional paradigms to new approaches: smart tourism planning - Josep Antoni Ivars-Baidal; José Fernando Vera Rebollo (Boletín de la Asociación de Geógrafos Españoles)
Tourism experiences remarkable transformations, as a consequence of factors such as technological evolution, changes in demand and the appearance of new business models. The interrelation of these dynamics with tourist destinations raises questions that affect planning and the evolution towards a more sustainable tourism. The consequent need for new approaches and paradigms of planning bases the present work. From a theoretical and conceptual approach, an evolutionary analysis of the tourism planning in Spain is carried out and different planning dimensions are discussed, such as the wear of the theoretical models of reference; the discredit of planning; the challenge of digitalization; the difficulty of applying new techniques, methods and sources of information; or the appearance of tourism dynamics in the local society that reconfigure the relations between residents and tourists. The article proposes the foundations of the smart planning of destinations as a new paradigm of tourism planning, due to its ability to bring together different processes and the possibility that this approach may lead to an accentuation of the role of the market in tourism planning, if there is no reflection on its nature and scope.